Ordinance No. 317: An Ordinance Concerning Offenses and Disorderly Conduct, THE DAILY ASTORIAN, Feb. 22, 1879, at 3, § 9 (Astoria, OR) - (:unkn) unknown (My University, 1879)
That any person or persons who shall carry any fire arms, knife, dirk, knuckles, slung-shot or any other dangerous weapon in a concealed manner about their or his person, within the corporate limits of the city, without a permit, which permit shall be issued by the auditor and clerk of the city upon the recommendation, in writing, of the chief of police, and upon the presentation of the treasurer's receipt, that the applicant therefore, has paid into the city treasurer the sum of five dollars for a yearly permit, or the sum of one dollar for a permit extending over the period of one month, shall upon conviction thereof before the police court, be fined not less than two nor more than twenty-five dollars, or by a term of imprisonment not exceeding twenty days, provided this section shall not apply to the officers of the law.
Keywords: CARRY - CONCEALED